Kajian Linguistik Modern Strukturalis dalam Pembelajaran Bahasa Arab - Rizki, Restu Budiansyah (Alsina : Journal of Arabic Studies, 2020)
Today's modern linguistic ideas seem very hot to be discussed on the conference stages. Its presence has brought fresh air for language and education activists. Not without reason, linguistics has contributed in breaking down various aspects of linguistic material to be transformed into foreign language learning, one of which is Arabic. this has been seen with the existence of a rainbow of linguistic studies in various lines of discussion. Call it one of the most famous modern linguistic studies today is structuralism. Structuralism tries to present a language lens that suppresses aspects of behaviorism and sees that language is obtained because of a trigger factor or continuous training. The method presented in this research is entitled library research. So that the data obtained comes from theories which in their discussion address structuralist modern linguistic studies and foreign language learning. The results showed that the realm of structuralist modern linguistics is very suitable to be applied in foreign language learning, one of which is Arabic. The suitability of these applications can be echoed by the following steps, including 1) practice repeating utterances in Arabic which can have an impact on students' habit of speaking in Arabic, 2) changing the type of sentence between isim or fi'il, 3) expansion exercises meaning in sentences with different patterns, and 4) connecting exercises.